53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-0735
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Jet Noise Source Locations with Acoustic Beamforming

Abstract: Numerous methods have been used by the aeroacoustics community to locate noise sources of different frequencies in subsonic jets. These include: acoustic mirrors, microphone arrays, two-microphone methods, causality correlation and coherence techniques, acoustic beamforming, and automated source breakdown. Except for the acoustic beamforming, most of these methods are quite time consuming. No one seems to have ever compared the performance of these techniques. This paper compares the performance of various exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…As can be seen in Fig. 6, the results obtained by the beamforming method are in good agreement with the results of [22], in which a similar method was used. The positions of the noise sources under similar outflow conditions practically coincide with each other for different jet installations.…”
Section: Experimental Study Of the Position Of Noise Sources Of A Tursupporting
confidence: 83%
See 4 more Smart Citations
“…As can be seen in Fig. 6, the results obtained by the beamforming method are in good agreement with the results of [22], in which a similar method was used. The positions of the noise sources under similar outflow conditions practically coincide with each other for different jet installations.…”
Section: Experimental Study Of the Position Of Noise Sources Of A Tursupporting
confidence: 83%
“…The results obtained for the jet outflowing from the conical nozzle were compared with the results of other authors and the expression for the Strouhal number from [22]. It was found that the position of the noise sources in the jet is close enough to the calculated one.…”
Section: Experimental Study Of the Position Of Noise Sources Of A Turmentioning
confidence: 60%
See 3 more Smart Citations